DAGHESTAN ECONOMY ON THE THRESHOLD OF A NEW STAGE OF REFORM - ALIEV, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2004)
For the Daghestan economy, as well as for the Russian economy as a whole, the 21st century has brought an end to the recession; a general stabilization and incipient growth of most macro economic indicators. But before we go on to examine the possible ways of economic recovery, let us make an assessment of the starting conditions for this new stage in the republic’s economic and social development. In the ten years of market reform, industrial output in Daghestan has fallen 4.5 times, including 1.52 times in engineering, 5.1 times in the food industry and 11.6 times in the light industry, while agricultural output has fallen 2.5 times. The final decade of the 20th century ended in a collapse of the republic’s economy and an unprecedented drop in the living standards of an overwhelming majority of its population. That was due, in the first place, to the institutional inability of the republic’s state-run economy to adjust to market conditions, its structural deficiencies and the unfavorable geopolitical conditions after the breakup of the U.S.S.R.t turned out that the republic’s industry and agriculture were less developed, less independent and more socialized than those of other RF constituencies. Moreover, Daghestan has turned out to be a region, on the one hand, lying close to the “hot spots” of the Caucasus and, on the other, far removed from the areas of real and potential economic growth in Russia.Internal factors, such as the highly uneven distribution of the productive forces, have also played an important role. Daghestan’s entire production potential is concentrated in the lowland and foothill zones, whereas in mountain areas there are no sufficiently developed industrial or agrarian structures that could enable their inhabitants to survive on their own in market conditions.These areas are characterized by a subsistence economy, a poorly developed production and social sphere and a harsh climate, especially in winter. Leaving these areas to fend for themselves in the new marketplace without any economic or social support would amount to putting them on the brink of extinction. Unequal conditions of economic activity largely explain the different “economic mentality” of the mountain peoples, which makes it necessary to develop a special tactics for introducing market relations. Today it is quite obvious that the failure to take measures facilitating the transition from the planned economy to a market economy was one of the most significant causes of the slump in economic activity in the 1990s. Daghestan’s development peculiarities have also resulted in greater vulnerability of the industrial organ-ism to radical reforms, which has manifested itself not only in the economy, but also in the field of domestic politics. The breakup of the Soviet Union has had an extremely painful effect on the republic. Once an in-ternal territory of the U.S.S.R., it has turned into a border region of Russia at the epicenter of tough geo-political pressure by some neighboring countries, and also by other states pursuing their interests in the Northern Caucasus. At the same time, the hopes that economic development in the republic would be intensified as it acquired the status of Russia’s “gateway "to the countries of the Middle East and South Asia have so far not been justified. On the contrary, the rupture of production ties between Russian business entities and enterprises in the Transcaucasian republics led to a sharp decline in freight traffic across the territory of Daghestan, contributing to an actual reduction in its “transport accessibility” in relation to other parts of the country. The situation in this sphere took a further turn for the worse with the development of the Chechen conflict. In fact, one could say there was a transport blockade of the republic, which naturally had an effect on the production performance of its enterprises, on interregional economic exchange and ultimately on its overall socioeconomic position. All these factors badly tarnished the economic image of the region and reduced its investment attractive-ness. As a result, the republic lost a significant part of the financial infusions into its economy, which was one of the main causes of long-term stagnation. In the 1990s, most of the key indicators of economic and social development in Daghestan exceeded the critical levels accepted in world practice, reflecting the emergence of a number of extremely negative trends (see Table 1).